STRATEGI KOMUNIKASI PEMASARAN DAYA TARIK WISATA ALAS KEDATON DI DESA KUKUH - I Gusti Ngurah Putu Dedy Wirawan; I Nyoman Yoga Segara; I Nyoman Alit Putrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The management of Alas Kedaton tourism object is managed by the village so that the promotion has not been maximized, within five years the visitors of the archipelago have decreased while foreign visitors have experienced fluctuations, currently promotions only use brochures, as well as the lack of the government's role in marketing and infrastructure, issues that must be studied 1) what is the form of marketing communication for Alas Kedaton tourism object in Kukuh Village, Marga, Tabanan? 2) how can a marketing communication strategy be used to increase visitors? 3) what are the implications of integrated marketing communication (IMC) and the SOSTAC model. The results of the study found that the manager of Alas Kedaton tourism object must 1) Horizontal coordination between stakeholders is not optimal. Each stakeholder is still focused on his own business, (2) communication that focuses on the marketing mix has not been implemented, and (3) to establish good communication with the government regarding infrastructure development and promotion and to take advantage of village proximity. The heads of clans together with the government in an effort to help oversee information, submit proposals and promotions through online media. The implications of the Alas Kedaton tourism object marketing communication strategy in seeking communication effectiveness by considering the influence of communication include: 1) cognitive, namely eliminating ambiguity, forming attitudes and convincing the public about the products, media to be used in advertising planning. 2) affective to find feelings, attitudes, behaviors, and emotions in buying products offered by managers of Alas Kedaton tourism object. 3) behavior to determine intention or behavior in buying products offered at Alas Kedaton tourist attractions.Â